The Role of Hiss, Chorus, and EMIC Waves in the Modeling of the Dynamics of the Multi‐MeV Radiation Belt Electrons. Issue 9 (7th September 2020) - Drozdov, A. Y.; Usanova, M. E.; Hudson, M. K.; Allison, H. J.; Shprits, Y. Y.
Abstract: In this study, we performed a series of long‐term and individual storm simulations with and without hiss, chorus, and electromagnetic ion cyclotron (EMIC) waves. We compared simulation results incorporating different wave modes with Van Allen Probes flux observations to illustrate how hiss and chorus waves aid EMIC waves in depleting multi‐MeV electrons. We found that EMIC, hiss, and chorus waves are required to reproduce satellite measurements in our simulations. Our results indicate that hiss waves play a dominant role in scattering near‐equatorial mirroring electrons, and they assist EMIC waves, which scatter only small pitch angle electrons. The best agreement between the observations and the simulations (long‐term and 17 January 2013 storm) is achieved when hiss, chorus, and EMIC waves are included. Key Points: Hiss and chorus waves aid EMIC waves in depleting near equatorial mirroring electrons In the presence of EMIC waves, chorus wave‐particle interactions can result in a net loss instead of acceleration of multi‐MeV electrons In long‐term simulations, hiss waves play a dominant role in aiding multi‐MeV electron depletion by EMIC waves